Aplicação de modelagem de processos de negócios na determinação de direcionadores de custo de mão-de-obra em um sistema de produção e colheita de cana-de-açúcar - Costa, Eugênio Pacceli (2010)
Sugar industries usually deal with several problems in their operations mainly due to the seasonal nature of their production. Furthermore, they also face many administrative difficulties, particularly in issues surrounding labor and manpower hiring. Such occupations require a broad range of abilities, including manual labor jobs and jobs which require skilled technician duties. These factors associated to the stable nature of the sugar cane culture cause huge complications in its cost accounting. The purpose of this work is to examine the use of action research methodology as well as methods and techniques of business processes modeling to identify manpower cost drivers and to support a system development for distribution and allocation automation of these costs within the accounting.